Social Criticism In John Lennon’s Selected Songs: A Genetic Structuralism Analysis - Muhammad Habibi; Lynda Susana Widya Ayu Fatmawaty; Eni Nur Aeni (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2025)
This research aims to examine the social criticism in John Lennon’s selected songs, namely “Imagine,” “Gimme Some Truth,” and “Give Peace a Chance.” The study explores how John Lennon navigated his worldview and personal experiences, shaped by the issues he faced, to create songs that serve as a form of social criticism addressing societal problems. The primary research question focuses on identifying the social criticisms embedded in John Lennon’s selected songs. By analyzing the relationship between the reasons behind the creation of these works and their intrinsic elements, such as lyrics, song structure, and diction, this research aims to uncover the depiction of social criticism in the selected songs and delve deeper into Lennon’s perspectives on social issues, politics, and human rights. The findings are expected to contribute to a better understanding of the implementation of social criticism in popular works such as songs. This research not only enhances theoretical knowledge in the field of genetic structuralism but also provides insights into the importance of critical thinking regarding social issues in society